2002
DOI: 10.1177/014616720202800704
|View full text |Cite
|
Sign up to set email alerts
|

When Prosperity Breeds Intergroup Hostility: The Effects of Relative Deprivation and Relative Gratification on Prejudice

Abstract: In previous theory and research dealing with relative deprivation (RD), the role of relative gratification (RG), the opposite of RD, was relatively overlooked. Two experiments (N = 245) tested the impact of both RD and RG on prejudice toward socially significant outgroups. Experiment 1 manipulated temporal RD and RG by confronting participants to declining (RD) or improving (RG) job opportunities and found no effect of RD on prejudice but reliable effects of RG. Experiment 2 manipulated group RD and RG and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
1
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 46 publications
9
80
1
6
Order By: Relevance
“…In Australia, Johnson, Terry, and Louis (2005) showed that white people's prejudice towards Asian immigrants increased the more the whites considered their superior social status legitimate, and the more they perceived the instability of their own social status' superiority. Guimond and Dambrun (2002) and Mackie, Devos, and Smith (2000) reported similar findings, which they explained with the theory of relative gratification. According to this theory, when positive outcomes for those belonging to the in-group emerge from an intergroup confrontation, the in-group members may be motivated to adopt discriminatory attitudes towards the out-group in order to preserve the positive social identity resulting from the confrontation.…”
Section: Discussionsupporting
confidence: 66%
“…In Australia, Johnson, Terry, and Louis (2005) showed that white people's prejudice towards Asian immigrants increased the more the whites considered their superior social status legitimate, and the more they perceived the instability of their own social status' superiority. Guimond and Dambrun (2002) and Mackie, Devos, and Smith (2000) reported similar findings, which they explained with the theory of relative gratification. According to this theory, when positive outcomes for those belonging to the in-group emerge from an intergroup confrontation, the in-group members may be motivated to adopt discriminatory attitudes towards the out-group in order to preserve the positive social identity resulting from the confrontation.…”
Section: Discussionsupporting
confidence: 66%
“…Brown (2000) specifically proposed in his overall assessment of SIT that one major challenge is that of identifying the conditions under which ingroup bias is associated with outgroup derogation. Contrary to a number of theoretical perspectives, there are reasons to believe that a favourable group comparison may be one such condition (see Guimond & Dambrun, 2002). The social identity analysis of intergroup relations relies heavily on the functioning of social comparison processes (Brown, 2000;Oakes, Haslam, & Turner, 1994).…”
Section: Outgroup Derogation: the Effects Of Favourable Group Outcomesmentioning
confidence: 99%
“…Guimond and Dambrun (2002) examined the role of both RD and RG and predicted that, in addition to an effect of RD, RG would also generate higher levels of prejudice. It was argued that a condition of RG, by putting individuals in a privileged position (see Kawakami & Dion, 1995), would trigger the need to maintain or to justify such privileges and that prejudice (or outgroup derogation) would be used to provide such justification.…”
Section: Outgroup Derogation: the Effects Of Favourable Group Outcomesmentioning
confidence: 99%
“…Another aspect that was measured were feelings of temporal relative deprivation (Crosby, 1976;Guimond & Dambrun, 2002;Runciman, 1966) ('In relation to 2009 my family's financial situation is today in a [1 = much worse, 7 = much better] condition') and in relation to what people feel they deserve ('I believe that I deserve much more than what I have at the moment'). We also assessed feelings of personal economic vulnerability with 5 items as in Staerklé, Delay, Gianettoni and Roux (2007).…”
Section: Methodsmentioning
confidence: 99%